Vertical Transmission of Coronavirus Disease 2019: A Case Report - Kamran Dehghan; Sakineh Aghazadeh (Mashhad University of Medical Sciences, 2021)
Background: Coronavirus disease 2019 (COVID-19) is an emerging viral disease with a high rate of transmissibility that has spread and become the first pandemic of the century. There are limited data available regarding COVID-19 during pregnancy. An important question is whether pregnant mothers transmit the virus to their fetuses or newborns. Case report: This study was conducted to investigate the vertical transmission of the COVID-19 virus from pregnant mothers to fetuses. This study reported the case of a preterm newborn admitted to the neonatal intensive care unit of Imam Khomeini Hospital Urmia, Iran, from a COVID-19-positive mother with severe respiratory illness. A preterm female newborn with a gestational age of 34 weeks, 1,800 g weight, and 1-minute and 5-minute Apgar scores of 4 and 5, respectively, was born through the emergency cesarean section from a 39-year-old gravid 1 mother. She was positive for COVID-19, in two consecutive reverse transcription polymerase chain reaction tests which were performed 48 h apart from each other. Conclusion:According to the limited available documents of our case, the researchers claimed that vertical transmission of COVID-19 was possible at this time.